Pengaruh Sarapan Terhadap Prestasi Pada Siswa - Zikra Hayati; Zuheri Ilyas (Indonesia, 2019)
Education is very important for the survival of a country / nation. Each student is required to get a satisfactory value in learning activities in each semester. Breakfast can indirectly improve learning achievement through its role in influencing concentration, memory, and brain growth. This study aims to determine the effect of breakfast on learning achievement in students at the 1st Lhokseumawe State Madrasah in 2018. This type of research is analytic with the Cross Sectional approach. The sampling technique used in this study was simple random sampling with a population of 744 respondents and obtained a sample of 260 respondents. This research instrument uses a questionnaire. Data collection was carried out from 1 August to 3 August 2018 in the Madrasah Tsanawiyah Negeri 1 Lhokseumawe City. The results of data collection showed that students who did not have good breakfast skills were 52 students (20%) and those who had good breakfast habits were 208 students (80%). The results of the analysis test obtained by the value of chi square p value = 0,000 <α = 0.05, so it can be concluded that there is an effect of breakfast on the achievement of the students of Madrasah Tsanawiyah Negeri 1 Lhokseumawe. It is expected that students can routinely consume a nutritious breakfast in order to achieve optimal performance.